Study on the Influence and Mechanism of Mineral Admixtures and Fibers on Frost Resistance of Slag–Yellow River Sediment Geopolymers - Ge Zhang; Huawei Shi; Kunpeng Li; Jialing Li; Enhui Jiang; Chengfang Yuan; Chen Chen (Nanomaterials, 2025)
To address the demands for resource utilization of Yellow River sediment and the durability requirements of engineering materials in cold regions, this study systematically investigates the mechanisms affecting the frost resistance of slag-Yellow River sediment geopolymers through the incorporation of mineral admixtures (silica fume and metakaolin) and fibers (steel fiber and PVA fiber). Through 400 freeze-thaw cycles combined with microscopic characterization techniques such as SEM, XRD, and MIP, the results indicate that the group with 20% silica fume content (SF20) exhibited optimal frost resistance, showing a 19.9% increase in compressive strength after 400 freeze-thaw cycles. The high pozzolanic reactivity of SiO2 in SF20 promoted continuous secondary gel formation, producing low C/S ratio C-(A)-S-H gels and increasing the gel pore content from 24% to 27%, thereby refining the pore structure. Due to their high elastic deformation capacity (6.5% elongation rate), PVA fibers effectively mitigate frost heave stress. At the same dosage, the compressive strength loss rate (6.18%) and splitting tensile strength loss rate (21.79%) of the PVA fiber-reinforced group were significantly lower than those of the steel fiber-reinforced group (9.03% and 27.81%, respectively). During the freeze-thaw process, the matrix pore structure exhibited a typical two-stage evolution characteristic of “refinement followed by coarsening”: In the initial stage (0–100 cycles), secondary hydration products from mineral admixtures filled pores, reducing the proportion of macropores by 5–7% and enhancing matrix densification; In the later stage (100–400 cycles), due to frost heave pressure and differences in thermal expansion coefficients between matrix phases (e.g., C-(A)-S-H gel and fibers), interfacial microcracks propagated, causing the proportion of macropores to increase back to 35–37%. This study reveals the synergistic interaction between mineral admixtures and fibers in enhancing freeze–thaw performance. It provides theoretical support for the high-value application of Yellow River sediment in F400-grade geopolymer composites. The findings have significant implications for infrastructure in cold regions, including subgrade materials, hydraulic structures, and related engineering applications.